Wildfire-specific Fine Particulate Matter and Risk of Hospital Admissions in Urban and Rural Counties. Issue 1 (January 2017) - Liu, Jia Coco; Wilson, Ander; Mickley, Loretta J.; Dominici, Francesca; Ebisu, Keita; Wang, Yun; Sulprizio, Melissa P.; Peng, Roger D.; Yue, Xu; Son, Ji-Young; Anderson, G. Brooke; Bell, Michelle L.
Abstract : Background: The health impacts of wildfire smoke, including fine particles (PM2.5 ), are not well understood and may differ from those of PM2.5 from other sources due to differences in concentrations and chemical composition. Methods: First, for the entire Western United States (561 counties) for 2004–2009, we estimated daily PM2.5 concentrations directly attributable to wildfires (wildfires-specific PM2.5 ), using a global chemical transport model. Second, we defined smoke wave as ≥2 consecutive days with daily wildfire-specific PM2.5 > 20 μg/m 3, with sensitivity analysis considering 23, 28, and 37 μg/m 3 . Third, we estimated the risk of cardiovascular and respiratory hospital admissions associated with smoke waves for Medicare enrollees. We used a generalized linear mixed model to estimate the relative risk of hospital admissions on smoke wave days compared with matched comparison days without wildfire smoke. Results: We estimated that about 46 million people of all ages were exposed to at least one smoke wave during 2004 to 2009 in the Western United States. Of these, 5 million are Medicare enrollees (≥65 years). We found a 7.2% (95% confidence interval: 0.25%, 15%) increase in risk of respiratory admissions during smoke wave days with high wildfire-specific PM2.5 (>37 μg/m 3 ) compared with matched non smoke wave days. We did not observe an association between smoke wave days with wildfire-specific PM2.5 ⩽ 37 μg/m 3 and respiratory or cardiovascular admissions. Respiratory effects of wildfire-specific PM2.5 may be stronger than that of PM2.5 from other sources. Conclusion: Short-term exposure to wildfire-specific PM2.5 was associated with risk of respiratory diseases in the elderly population in the Western United States during severe smoke days. See video abstract at, http://links.lww.com/EDE/B137 . Abstract : Supplemental Digital Content is available in the text.